STANDAR KOMPETENSI JABATAN ASN (STUDI PADA JABATAN PIMPINAN TINGGI PRATAMA DI LINGKUNGAN INSPEKTORAT KABUPATEN MAJALENGKA PROVINSI JAWA BARAT) - Rohmadin, Sulthon; Batubara, Yusi Eva (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2019)
In line with the President Jokowi’s Government Vision for the 2019-2024 period which focuses on “Excellent human Resources”, the bureaucratic reform requires the structuring and strengthening of apparatus resources, one of which is through ASN position competency standards. Job competency standards are used for employee procurement, appointment in office, promotion, transfer between positions, career development and awards for ASN. The method used in this study is tailor made method combined with FGD (expert meeting) method with related bureaucratic apparatus, and Delphi technique, which is one of the techniques for involving stakeholders in decision making/policy by gathering opinions through questionnaires/questionnaire. This study resulted in the concept of competency standards for high-level leadership positions in the Majalengka Regency Inspectorate consisting of managerial competencies (8 competencies), socio-cultural competencies (1 competency), technical competencies (8 competencies) and government competencies (17 competencies)